2023
DOI: 10.1097/md.0000000000034062
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of clinical prediction model for hemorrhoid recurrence after procedure for prolapse and hemorrhoids

Abstract: This study aimed to establish a clinical model to predict the risk of hemorrhoid recurrence after procedure for prolapse and hemorrhoids. The clinical data of patients who underwent stapler hemorrhoidal mucosal circumcision in Shanxi Bethune Hospital from April 2014 to June 2017 were collected retrospectively and followed up regularly after the operation. Finally, 415 patients were included, which were divided into training group (n = 290) and verification group (n = 125). Logistic regression method was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Based on the anal cushion descent theory, the procedure for PPH is designed to reposition and fix the descended cushions to their anatomical position, particularly in patients with Grade III and IV internal hemorrhoids. [19][20][21][22] Another minimally invasive technology, DG-HAL, has shown particular utility in treating Grade III and IV internal and mixed hemorrhoids. However, studies have indicated that PPH may result in long-term adverse effects, including high recurrence rates, rectal perforation, and pelvic abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the anal cushion descent theory, the procedure for PPH is designed to reposition and fix the descended cushions to their anatomical position, particularly in patients with Grade III and IV internal hemorrhoids. [19][20][21][22] Another minimally invasive technology, DG-HAL, has shown particular utility in treating Grade III and IV internal and mixed hemorrhoids. However, studies have indicated that PPH may result in long-term adverse effects, including high recurrence rates, rectal perforation, and pelvic abscesses.…”
Section: Discussionmentioning
confidence: 99%